2022
DOI: 10.4103/jfmpc.jfmpc_1717_21
|View full text |Cite
|
Sign up to set email alerts
|

Perception, burden and satisfaction of parents of children attending online classes during COVID-19 lockdown: A cross-sectional survey

Abstract: Introduction: Coronavirus has spread havoc globally, resulting in the closure of all sectors including education. Therefore, to continue a child’s learning, the government started online classes from home by involving parents. This new learning method might be hectic and challenging for parents; therefore, this study aimed to assess the perception, burden, and satisfaction of parents of children attending online classes. Methods: A cross-sectional onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…The study finding is similar with the study conducted in India which reported that 53% of parents are satisfies with technical support whose children were attended online classes during COVID-19. 9,16 Likewise, findings in school level instructional support 59.8%, online course management 58.2%, social interaction during online class 59.9% and overall education regarding online class 57.1% which is similar to the finding of the study conducted in USA. 10 The finding of this study revealed that there was significant association between the level of satisfaction regarding online class of their children with parents' education (p<0.001).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The study finding is similar with the study conducted in India which reported that 53% of parents are satisfies with technical support whose children were attended online classes during COVID-19. 9,16 Likewise, findings in school level instructional support 59.8%, online course management 58.2%, social interaction during online class 59.9% and overall education regarding online class 57.1% which is similar to the finding of the study conducted in USA. 10 The finding of this study revealed that there was significant association between the level of satisfaction regarding online class of their children with parents' education (p<0.001).…”
Section: Discussionsupporting
confidence: 83%
“…A similar study conducted in India concluded that 50% of the parents had satisfaction regarding online education. 9 Hence estimating a prevalence of 50% and using the Cochran's equation, 95% confidence Interval, 7% error was calculated the required sample size was 216. The participants were selected by purposive sampling technique.…”
Section: Methodsmentioning
confidence: 99%
“…These findings supported the results of the studies of Agaton and Cueto (2021) which showed that the parents agree with the effectiveness of the implemented educational policies to contain the pandemic. This is also in line with the findings of Rathaliya et al (2022), who revealed and identified that the parents' perception of online classes was positive, and they experienced a moderate-to-severe burden. In connection with the findings of the current study that found out that the overall educational program of the school is desired by most of the parents, this indicates that the school is doing well with their overall educational program in the delivery of online learning that still yielded in recommending online learning by most of the parents.…”
Section: Perception Of Parents Of the Delivery Of Online Learningsupporting
confidence: 90%
“…Agaton and Cueto (2021) revealed in their study that the parents agree with the effectiveness of the implemented educational policies to contain the pandemic. Rathaliya, et al (2022) also revealed and identified that the parents' perception of online classes was positive, and they experienced a medium-to-heavy burden. They also expressed great satisfaction with how well their educational goals were met during the COVID-19 pandemic.…”
Section: Parents and Online Learningmentioning
confidence: 98%
“…Other than the amplified domestic violence, the very bodies, strength, and management of time of women were challenged and were put to the test. For instance, the closure of the schools and the transition to online classes became a burden to many parents or guardians at home [11]. This means additional work for those involved in the child's education at home.…”
Section: Introductionmentioning
confidence: 99%